Tales on the radio in Western Africa. A pragmatic of the Orality for entire Development in Africa? Study of the case of radio Parana in Mali - (:unkn) unknown (My University, 2010)
How and why mass media can contribute to help and to question the orality that belongs to African societies? To answer this question, we are bound to carry out some sort of survey of speaking and language activities pertaining to modes of communication and information. The chosen field of investigation concerns the countries of Sahel, specifically the Bwa populations of Mali. It is in this geographical area that we try to check the hypothesis according to which the radio contributes to valorise and to save the oral, immaterial patrimony and constitutes one of the bridges of social, cultural, economic and political development of the African countries that receive it. The aim is to shed light on the ways in which mass media can invest societies characterised by oral tradition. Taking the example of tales which are told on the radio we can discover specific modes of appropriation. By interviewing storytellers, feeling of how media actors perform and questioning the way local radios work, by consulting reports from UNESCO and other associations, documents in information and communication sciences, but also anthropological and linguistic documents, it is at stake to understand that more media communication may lead to more common ground between human beings.
Keywords: African Research